2017
DOI: 10.1186/s12906-017-1984-9
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of propolis and its constituent caffeic acid phenethyl ester inhibit breast cancer cells proliferation in inflammatory microenvironment by inhibiting TLR4 signal pathway and inducing apoptosis and autophagy

Abstract: BackgroundPropolis and its major constituent – caffeic acid phenethyl ester (CAPE) have good abilities on antitumor and anti-inflammation. However, little is known about the actions of propolis and CAPE on tumor in inflammatory microenvironment, and inflammatory responses play decisive roles at different stages of tumor development. To understand the effects and mechanisms of ethanol-extracted Chinese propolis (EECP) and its major constituent - CAPE in inflammation-stimulated tumor, we investigated their effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 33 publications
1
64
0
4
Order By: Relevance
“…ROS are involved in cell oxidative stress mechanisms, predominantly via the induction of lipid peroxidation in the phospholipid membrane, the production of oxygen radicals and the induction of cell apoptosis ( 26 , 27 ). Antioxidant enzymes, such as SOD and GSH, eliminate ROS to maintain the balance of ROS generation and elimination during cell normal metabolism ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS are involved in cell oxidative stress mechanisms, predominantly via the induction of lipid peroxidation in the phospholipid membrane, the production of oxygen radicals and the induction of cell apoptosis ( 26 , 27 ). Antioxidant enzymes, such as SOD and GSH, eliminate ROS to maintain the balance of ROS generation and elimination during cell normal metabolism ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the role of oxidative stress, studies have indicated that the underlying molecular mechanisms of ethanol-induced gastric diseases may involve multiple signaling pathways, including apoptosis and mitogen-activated protein kinase (MAPK) pathways, such as extracellular signal-regulated kinase (ERK)1, ERK2, c-Jun N-terminal kinase (JNK) and p38 kinase (p38) MAPK pathways ( 26 , 27 ). Apoptosis is induced by oxidative stress and the subsequent increases in superoxide and hydroxyl radicals, and MAPK pathways have important roles in cell proliferation, differentiation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper sustains that caffeic acid phenethyl ester is rather most efficient than caffeic acid, inducing cell cycle arrest in S phase and triggering apoptosis in the triple-negative human Caucasian breast adenocarcinoma line cells (MDA-MB-231) [20]. In a similar report, caffeic acid phenethyl ester inhibited breast cancer MDA-MB-231 cells proliferation, activating apoptosis and autophagy, and inhibiting TLR4 signaling pathway [21]. The antiproliferative and proapoptotic activity of Lebanese propolis was demonstrated on breast adenocarcinoma MDA-MB-231 cells, Jurkat leukemic T-cells and glioblastoma U251 cells [16].…”
Section: Introductionmentioning
confidence: 79%
“…It has been demonstrated that CAPE can cause acetylated histones accumulation in MDA-MB-231 (ER-/PR-/Her2-) and MCF-7 (ER+) cells, which is associated with up-regulated ER and downrelulated EGFR in MDA-MB-231 cells and decreased ER and PR in MCF-7 cells. This evidence provides a potential mechanistic basis for propolis activity in breast cancer, which can be optimized for therapeutic intervention in cancer [86,87]. In addition, the results of in vivo and in vitro studies suggest that chrysin in both Chinese propolis and Brazilian green propolis may inhibit tumor cell progression and may be useful as a protential chemotherapeutic or chemopreventive antitumor reagent [88].…”
Section: Journal Of Food and Nutrition Researchmentioning
confidence: 99%